2023
DOI: 10.1101/2023.10.03.560720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Type I IFN signaling in the absence of IRGM1 promotesM. tuberculosisreplication in immune cells by suppressing T cell responses

Sumanta K. Naik,
Michael E. McNehlan,
Yassin Mreyoud
et al.

Abstract: Polymorphisms in theIRGMgene are associated with susceptibility to tuberculosis in humans. A murine ortholog ofIrgm,Irgm1, is also essential for controllingMycobacterium tuberculosis(Mtb) infection in mice. Multiple processes have been associated with IRGM1 activity that could impact the host response to Mtb infection, including roles in autophagy-mediated pathogen clearance and expansion of activated T cells. However, what IRGM1-mediated pathway is necessary to control Mtb infectionin vivoand the mechanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Neutrophils act as the body's rst line of defense against infection and respond to diverse in ammatory cues, including cancer. Although the role of IRGM1 in neutrophils in cancer scenarios remains to be investigated, based on the recent study that the IRGM1 is required to promote T cell-mediated control of infection in neutrophils [40], and on our results that IRGM1 + neutrophils express high levels of CXCL2, CXCL10, and CXCR2, chemokines and receptors involved in neutrophil recruitment and T cell activation, we reasonably postulate that the IRGM1 + neutrophils promote anticancer immunity. Though it is largely unknown how CCR8 blockade with UIPG0521m resulted in increased in ltration of IRGM1 + neutrophils, a study with an in ammatory disease model indicated that CCR8 de ciency reduced eosinophil accumulation but accelerated neutrophil accumulation in the in ammatory site, suggesting that CCR8 blockade may promote neutrophil accumulation [41].…”
Section: Discussionmentioning
confidence: 65%
“…Neutrophils act as the body's rst line of defense against infection and respond to diverse in ammatory cues, including cancer. Although the role of IRGM1 in neutrophils in cancer scenarios remains to be investigated, based on the recent study that the IRGM1 is required to promote T cell-mediated control of infection in neutrophils [40], and on our results that IRGM1 + neutrophils express high levels of CXCL2, CXCL10, and CXCR2, chemokines and receptors involved in neutrophil recruitment and T cell activation, we reasonably postulate that the IRGM1 + neutrophils promote anticancer immunity. Though it is largely unknown how CCR8 blockade with UIPG0521m resulted in increased in ltration of IRGM1 + neutrophils, a study with an in ammatory disease model indicated that CCR8 de ciency reduced eosinophil accumulation but accelerated neutrophil accumulation in the in ammatory site, suggesting that CCR8 blockade may promote neutrophil accumulation [41].…”
Section: Discussionmentioning
confidence: 65%